Biomass study of Anabaena sphaerica cultivated in electroplating industrial effluent - Yasodha. T , Dr.; M, Abi; M, Ishwarya (International Journal of Biological Research, 2024)
The growth of microalga Anabaena sphaerica in electroplating industrial effluent with reference to the vegetative cells , heterocysts and dry biomass weight brings about oxygenation and mineralization in addition to the increase in biomass which serve as a multipurpose raw material to the industries. From lab scale experiments it is demonstrated that the present investigation could be converted to pilot study for large scale production of biofuel and other commodity chemicals. Cultivation of microalgal biomass as a potential resource / raw material for various industries to produce commodity chemicals could enhance the economy and curtail the environmental hazards.